2012
DOI: 10.1111/j.1558-5646.2011.01560.x
|View full text |Cite
|
Sign up to set email alerts
|

Deep Under the Sea: Unraveling the Evolutionary History of the Deep-Sea Squat Lobster Paramunida (Decapoda, Munididae)

Abstract: The diversification of Indo-Pacific marine fauna has long captivated the attention of evolutionary biologists. Previous studies have mainly focused on coral reef or shallow water-associated taxa. Here, we present the first attempt to reconstruct the evolutionary history-phylogeny, diversification, and biogeography-of a deep-water lineage. We sequenced the molecular markers 16S, COI, ND1, 18S, and 28S for nearly 80% of the nominal species of the squat lobster genus Paramunida. Analyses of the molecular phylogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 74 publications
4
50
0
Order By: Relevance
“…Recent studies based on the munidid squat-lobster genus Paramunida suggest that dramatic environmental change may provide great geological and habitat complexity, which in turn promotes isolation and rapid diversification [78]. The fact that both families, chirostylids and munidids, diverged during the Late Triassic (see Figure 4) and currently occupy deep-sea habitats suggests that similar geological and environmental changes may also have driven major diversification within the Munididae, which shifted habitats at some point because the Jurassic forms are nearly all coral-reef associated.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies based on the munidid squat-lobster genus Paramunida suggest that dramatic environmental change may provide great geological and habitat complexity, which in turn promotes isolation and rapid diversification [78]. The fact that both families, chirostylids and munidids, diverged during the Late Triassic (see Figure 4) and currently occupy deep-sea habitats suggests that similar geological and environmental changes may also have driven major diversification within the Munididae, which shifted habitats at some point because the Jurassic forms are nearly all coral-reef associated.…”
Section: Discussionmentioning
confidence: 99%
“…However, the evolutionary value of the different morphological characters must be determined in a wide study on the phylogeny of the family Munididae. This study (actually in progress) would solve the extreme morphological convergence and heterogeneity in the divergence values within genera and species Cabezas et al 2012).…”
Section: Depth Range (M) Geographic Distributionmentioning
confidence: 98%
“…This close relationship has been confirmed by molecular evidence that have rendered this new genus as the sister group of Paramunida (Cabezas et al 2012, Cabezas and Chan 2014). Hendersonida gen. n. may be easily differentiated from Paramunida by having the dorsal surface of the carapace covered by granules and the distomesial spine of the antennal article 2 almost reaching the end of anterior prolongation of article 1.…”
Section: Family Munididae Ahyong Baba Macpherson and Poore 2010mentioning
confidence: 62%
“…Interestingly, the species Paramunida granulata (Henderson, 1885) is unique in having a granulated carapace and the distomesial spine of antennal article 2 very long, almost reaching the end of the anterior prolongation of article 1 (Baba 1988; Cabezas et al 2010). A previous phylogenetic study reported this species as the earliest offshoot within the genus in the early Oligocene (Cabezas et al 2012), which along with the above-mentioned marked morphological differences and a high genetic divergence indicate that this species followed an independent evolutionary trajectory (Cabezas et al 2010; Cabezas et al 2012; Machordom and Macpherson 2004). To reflect these findings, we herein propose a new genus, Hendersonida gen. n.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation